Carer coping and resident agitation as predictors of quality of life in care home residents living with dementia: Managing Agitation and Raising Quality of Life (MARQUE) English national care home prospective cohort study. (1st October 2018) - Laybourne, Anne; Livingston, Gill; Cousins, Sian; Rapaport, Penny; Lambe, Kate; La Frenais, Francesca; Savage, Hannah; Manela, Monica; Stringer, Aisling; Marston, Louise; Barber, Julie; Cooper, Claudia
Abstract : Objectives: The objectives of the study are (1) to test our primary hypothesis that carers using more dysfunctional coping strategies predict lower quality of life in care home residents living with dementia, and this is moderated by levels of resident agitation, and (2) to explore relationships between carer dysfunctional coping strategy use, agitation, quality of life, and resident survival. Methods: In the largest prospective cohort to date, we interviewed carers from 97 care home units (baseline, 4, 8, 12, 16 months) about quality of life (DEMQOL‐Proxy) and agitation (Cohen‐Mansfield Agitation Inventory) of 1483 residents living with dementia. At baseline, we interviewed 1566 carers about coping strategies (Brief COPE), averaging scores across care home units. Results: Carer dysfunctional coping strategies did not predict resident quality of life over 16 months (0.03, 95% CI −0.40 to 0.46). Lower resident quality of life was longitudinally associated with worse Cohen‐Mansfield Agitation Inventory score (−0.25, 95% CI −0.26 to −0.23). Survival was not associated with carer dysfunctional coping, resident quality of life, or agitation scores. Conclusions: Carer dysfunctional coping did not predict resident quality of life. Levels of resident agitation were consistently high and related to lower quality of life, over 16 months. Lack of association between carer dysfunctional coping and resident quality of life may reflect the influence of the care home or an insensitivity of aggregated coping strategy scores. The lack of relationship with survival indicates that agitation is not explained mainly by illness. Scalable interventions to reduce agitation in care home residents living with dementia are urgently needed.